Theory of Education and Philosophy - Villalobos Paniagua, Ricardo Antonio (2014)
The Theory of Education cannot be disengaged from Philosophy, so it is necessary for the teacher contemporary to have philosophical principles and concepts, be them anthropological or epistemological. The role of philosophy education gives to the teacher cognitive a input that enriches his or her teaching practice. This essay consideres such symbiosis as education-philosophy, elaborating on ideas that lead to reflection on the development of education as a theoretical process, and from this to pedagogical practice, which generates new didactic theories framed in the necessity that education in general indentifies in philosophy its epistemological and vital basis particularly in university teaching.